2021
DOI: 10.1177/15407969211053810
|View full text |Cite
|
Sign up to set email alerts
|

Skills, Behaviors, Expectations, and Experiences Associated with Improved Postsecondary Outcomes for Students with Significant Cognitive Disabilities

Abstract: An in-depth literature review was conducted to identify the skills, behaviors, expectations, and experiences (SBEEs) associated with employment, further education, and independent living for students with significant cognitive disabilities following high school. Analysis of 53 quantitative and qualitative studies identified 103 specific SBEEs associated with post high school outcomes. We then clustered the SBEEs into 10 constructs. We present the constructs and representative SBEEs, discuss implications for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Recent research identified self‐determination as having a significant influence on overall quality of life for students with intellectual disabilities (Mumbardó‐Adam et al, 2023). Self‐determination has been shown to directly promote positive outcomes in areas such as employment, community access, life skills, and financial independence (McConnell et al, 2021; Shogren, Wehmeyer, Palmer, Rifenbark, et al, 2015), in addition to academic outcomes (Gaumer Erickson et al, 2015). Additionally, self‐determination is a key mediating factor in post‐school life outcomes such as social relationships, emotional wellbeing, access to services, and health status for students with intellectual disabilities (Shogren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research identified self‐determination as having a significant influence on overall quality of life for students with intellectual disabilities (Mumbardó‐Adam et al, 2023). Self‐determination has been shown to directly promote positive outcomes in areas such as employment, community access, life skills, and financial independence (McConnell et al, 2021; Shogren, Wehmeyer, Palmer, Rifenbark, et al, 2015), in addition to academic outcomes (Gaumer Erickson et al, 2015). Additionally, self‐determination is a key mediating factor in post‐school life outcomes such as social relationships, emotional wellbeing, access to services, and health status for students with intellectual disabilities (Shogren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Literature from the past 50 years argues that students with ESN should be educated with their peers in inclusive environments (Brown et al, 1976;Brown et al, 1973), culminating in research that suggests that services in inclusive environments lead to more positive outcomes across all domains. For instance, when educated in general education classes, students with ESN have greater academic achievement (Gee et al, 2020), social outcomes (Jameson et al, 2022), post-school outcomes (McConnell et al, 2021), and growth in communication (Gee et al, 2020). In contrast, there are no experimental studies that document better outcomes for students with ESN when they receive services in segregated environments (e.g., self-contained classes; Gee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to federal legislation requiring instruction in the LRE, research demonstrates the benefits of education in inclusive, general education classrooms. For students with ESN, inclusion has been shown to result in more positive post-school outcomes (McConnell et al, 2021) and increased achievement in academic, communication, social, and adaptive domains (Carter & Hughes, 2005; Fisher & Meyer, 2002; Gee et al, 2020; McDonnell et al, 2003). In addition, placement in inclusive settings has been shown to increase student access to the general education curriculum and highly qualified teachers compared to separate placements (Kurth et al, 2019; Quirk et al, 2017; Soukup et al, 2007; Wehmeyer et al, 2003).…”
mentioning
confidence: 99%